Sensitivity of psychophysical measures to signal processor modifications in cochlear implant users - Drennan, Ward R. (2010)
Experienced users of the Clarion cochlear implant were tested acutely with the HiResolution (HiRes) and HiRes Fidelity120 (F120) processing strategies. Three psychophysically-based tests were used including spectral-ripple discrimination, Schroeder-phase discrimination and temporal modulation detection. Three clinical outcome measures were used including consonant-nucleus-consonant (CNC) word recognition in quiet, word recognition in noise and the clinical assessment of music perception (CAMP). Listener's spectral-ripple discrimination ability improved with F120, but Schroeder-phase discrimination was worse with F120 than with HiRes. Listeners who had better than average acuity showed the biggest effects. There were no significant effects of the processing strategy on any of the clinical abilities nor on temporal modulation detection. Additionally, the listeners' day-to-day clinical strategy did not appear to influence the result suggesting that experience with the strategies did not play a significant role. The results underscore the value of acoustic psychophysical measures through the sound processor as a tool in clinical research, because these measures are more sensitive to changes in the processing strategies than traditional clinical measures, e.g. speech understanding. The measures allow for the evaluation of sensitivity to specific acoustic attributes revealing the extent to which different processing strategies affect these basic abilities and could thus improve the efficiency of the development of processing strategies.